MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MATERI PERJUANGAN PADA MASA PENJAJAHAN BELANDA DAN JEPANG MELALUI MODEL PROBLEM BASED INSTRUCTIONS PADA SISWA KELAS VA SEKOLAH DASAR NEGERI 01 SURUH KECAMATAN TASIKMADU KABUPATEN KARANGANYAR SEMESTER II TAHUN PELAJARAN 2014/2015 - -, Sutardi (Widya Wacana: Jurnal Ilmiah, 2015)
The problem of this research is â€œCan problem based instruction model improve the study result ofsocial studies about the struggle during netherlands and japan colonization through problem basedinstruction model to the VA students in SDN 01 Suruh Tasikmadu Karanganyar semester II in theacademic year of 2014/2015â€.The purpose of this research is to improve the study result of social studies about the struggleduring netherlands and japan colonization through problem based instruction model to the VA students inSDN 01 Suruh Tasikmadu Karanganyar Semester II in the academic year of 2014/2015. This research isin the form of classroom action research. It is carried out in SDN 01 Suruh Tasikmadu Karanganyarsemester II in the academic year of 2014/2015. The subject of the research is the students of class VA SDN01 Suruh Tasikmadu Karanganyar that consists of about 25 students.This research is carried out for about 3 months, started on January until March 2015. The Dataresource of this research is students score and document. The data collecting method is observation anddocument analysis. The technique of validity test used the technique of data resource triangulation andmethod triangulation. The technique of data analysis used in this research is interactive analysistechnique.The result of this research is the conclusion that: problem based instruction model can improvethe study result of social studies about the struggle during netherlands and japan colonization throughproblem based instruction model to the VA students in SDN 01 Suruh Tasikmadu Karanganyar semester IIin the academic year of 2014/2015. It is proven by the students score. In the pre research their score is 65.Then, 68 in cycle I, 75 in cycle II and 82 in cycle III as well as determined in the indicator.Key words: Study Result, Problem based instruction, Social Studies.